An indirect treatment comparison (ITC) and matching-adjusted indirect comparison (MAIC) between a 15-valent (V114) and a 20-valent (PCV20) pneumococcal conjugate vaccine among healthy infants - Shahrul Mt-Isa; Justin R. Chumbley; Emma L. Crawford; Natalie Banniettis; Ulrike K. Buchwald; Jessica Weaver; Thomas Weiss (Taylor & Francis Group, 2023)
Objectives Immunogenicity between 15-valent V114 (PCV15) and 20-valent PCV20 pneumococcal conjugate vaccines in healthy infants is compared in an indirect treatment comparison and matching-adjusted indirect comparison. Hypotheses: immunogenicity of V114 is non-inferior to PCV20 for all PCV13 serotypes, and superior to PCV20 for serotype 3 based on lower bound margins. Methods Two phase 3 pivotal studies on 3 + 1 pediatric vaccination schedule at age 2, 4, 6, and 12-15 months compared V114 (N = 858) to PCV13 (N = 856) and PCV20 (N = 1001) to PCV13 (N = 987). Infant's age and race in V114 study were matched to those in PCV20 study. Primary endpoints were serotype-specific Immunoglobulin G (IgG) response rate difference (RRD) 30 days post-dose (PD)3; IgG geometric mean concentration (GMC) ratios 30 days PD3 and PD4. Results V114 was non-inferior (${\rm{margi}}{{\rm{n}}_{RRD}}$>-10%-point; ${\rm{margi}}{{\rm{n}}_{GMCratio}}$ >0.5) to PCV20 (p-value <0.001) for all endpoints. V114 was superior (${\rm{margi}}{{\rm{n}}_{RRD}}$ >0%-point; ${\rm{margi}}{{\rm{n}}_{GMCratio}}$ >1.2) to PCV20 (p-value <0.001) for serotype 3: RRD was 34.5% (95%CI 27.9%-41.1%) PD3, and IgG GMC ratios were 2.39 (95%CI 2.12-2.68) PD3 and 2.15 (95%CI 1.90-2.41) PD4. Conclusion Immune response to V114 administered in a 3 + 1 schedule in healthy infants was considered non-inferior to PCV20 for all 13 PCV13 serotypes and superior for serotype 3 PD3 and PD4. Clinical trial registration www.clinicaltrials.gov identifiers NCT03893448, NCT04382326